2013
DOI: 10.1016/j.jallcom.2013.03.054
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the post-annealing temperature on the growth mechanism of Bi2Sr2Ca1Cu2O8+ thin films produced on MgO (1 0 0) single crystal substrates by pulsed laser deposition (PLD)

Abstract: a b s t r a c tThe effects of post-annealing temperature were investigated on Bi 2 Sr 2 Ca 1 Cu 2 O 8+o thin films deposited on MgO (1 0 0) substrates by pulsed laser deposition (PLD). The structural and superconducting properties of the films have been determined by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), temperature depende nt resistivity (R-T), and DC magnetization measure ments. The films which were deposited at 600 °C were post-annealed in an atmosphere of a gas mixture of Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The calculation of critical current density for Bi-2212 thin film produced via PLD is a rare issue in the literature. However, all maximum J C values for the film produced are comparable and better than those of some other recent studies [20,31,32]. Calculated J C value of the thin film annealed for 30 min explicitly demonstrates a better performance with increasing magnetic field up to 1000 Oe, compared to those of other films and then it starts to decrease comparatively.…”
Section: Calculations Of Critical Current Densitysupporting
confidence: 68%
See 2 more Smart Citations
“…The calculation of critical current density for Bi-2212 thin film produced via PLD is a rare issue in the literature. However, all maximum J C values for the film produced are comparable and better than those of some other recent studies [20,31,32]. Calculated J C value of the thin film annealed for 30 min explicitly demonstrates a better performance with increasing magnetic field up to 1000 Oe, compared to those of other films and then it starts to decrease comparatively.…”
Section: Calculations Of Critical Current Densitysupporting
confidence: 68%
“…The films were firstly deposited on the preheated MgO substrate at 600 1C. Later on, post-annealing heat treatment has performed at 860 1C which was obtained as an optimum temperature in our previous study [20] in argon and oxygen (Ar:93, O 2 :7) atmosphere, for 10, 30, and 60 min. The postannealing heat treatments have been applied on those films for three different annealing times, in order to determine the optimum condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM measurements were performed on the bulk and the thin film samples to get more insight into the JC value with the decrease in the dimensionality of the sample. Figures 3(a In the case of the thin films grown by the PLD technique, the values of J C obtained in the present study were found to be comparable to those reported in the literature [28][29][30][31]. The enhancement in the value of J C with the decrease in the dimensionality of the sample from bulk to thin-film can be related to the microstructure of the superconductor.…”
Section: Field-dependent DC Magnetization Measurement (M-h)supporting
confidence: 85%
“…On the other hand, as it is well known Bi-2212 ceramic presents incongruent melting, producing different secondary phases as Bi-2201, CaCuO 2 , or (Sr,Ca)CuO 2 [31] after solidification. As a consequence, after the texturing process, it is necessary to perform a thermal treatment in order to form the Bi-2212 superconducting phase [32,33] from the secondary ones. This annealing process was performed under air, and consisted in two steps: 60 h at 860 ºC, followed by 12 h at 800 ºC and, finally, quenched in air to room temperature.…”
Section: Methodsmentioning
confidence: 99%